INTEGRATION OF INFORMATIONAL COMPUTER TECHNOLOGIES SMK: AUTOMATION OF THE MAIN FUNCTIONS OF THE TECHNICAL CONTROL DEPARTMENT - S. A. Pavlenko (Литьë и металлургия)
It is shown that automation of some functions of control department allows to record defects, reclamations and failures of technology, to make the necessary reporting forms and quality certificates for production.